A taxonomic note on Homorosoma horridulum Voss, 1958 (Coleoptera: Curculionidae), with new records from Taiwan - Korotyaev, Boris A.; Yoshitake, Hiraku; Huang, Junhao (Zootaxa, 2014)
Homorosoma horridulum Voss 1958 (Curculionidae: Ceutorhynchinae) was described from Kuatun, China, based on two specimens in the J. Klapperich collection. Since that time it has been uninvestigated for more than half a century, except by Colonnelli (2004), who listed it in his world catalogue of the subfamily. The recent examination of the holotype of H. horridulum revealed that it should be placed in the genus Scleropteroides Colonnelli 1979. In addition, Scleropteroides specimens from Taiwan agree well with the holotype of H. horridulum not only in general appearance but also in male genital structures. Here we transfer Homorosoma horridulum Voss 1958 to the genus Scleropteroides Colonnelli 1979 as Scleropteroides horridulus (Voss 1958) and record the species from Taiwan for the first time. Depositories of specimens examined are abbreviated as follows: CMNC: Canadian Museum of Nature, Ottawa; CWOB: C.W. O’Brien collection, Green Valley, Arizona, USA; EUMJ: Laboratory of Environmental Entomology, Faculty of Agriculture, Ehime University, Matsuyama, Japan; NIAES: National Institute for Agro-Environmental Sciences, Tsukuba, Japan; SMNH: Swedish Museum of Natural History, Stockholm, Sweden; and ZIN: Zoological Institute, Russian Academy of Sciences, St. Petersburg, Russia. Before going further, we wish to express our cordial thanks to R. S. Anderson, François Génier (CMNC), H. Kojima (Tokyo University of Agriculture), M. Sakai (Ehime University), C.W. O’Brien, and B. Viklund (SMNH) for the loan or donation of specimens examined. The first author thanks the late P. Lindskog (SMNH) for the help during his first visit to Stockholm. The study by the first author was supported by Grant No 13-04-01002 from the Russian Foundation for Basic Research.